Annotation and cluster analysis of spatiotemporal- and sex-related lncRNA expression in rhesus macaque brain - Liu, Siling; Wang, Zhengbo; Chen, Dong; Zhang, Bowen; Tian, Ren-Rong; Wu, Jing; Zhang, Ying; Xu, Kaiyu; Yang, Liu-Meng; Cheng, Chao; Ma, Jian; Lv, Longbao; et al.

(untitled) (Genome Research, 2017)
Long noncoding RNAs (lncRNAs) mediate important epigenetic regulation in a wide range of biological processes and diseases. We applied comprehensive analyses of RNA-seq and CAGE-seq (cap analysis of gene expression and sequencing) to characterize the dynamic changes in lncRNA expression in rhesus macaque (Macaca mulatta) brain in four representative age groups. We identified 18 anatomically diverse lncRNA modules and 14 mRNA modules representing spatial, age, and sex specificities. Spatiotemporal- and sex-biased changes in lncRNA expression were generally higher than those observed in mRNA expression. A negative correlation between lncRNA and mRNA expression in cerebral cortex was observed and functionally validated. Our findings offer a fresh insight into spatial-, age-, and sex-biased changes in lncRNA expression in macaque brain and suggest that the changes represent a previously unappreciated regulatory system that potentially contributes to brain development and aging.